2022
DOI: 10.3389/fpls.2022.1006991
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling and gene expression analyses provide insights into cold adaptation of an Antarctic moss Pohlia nutans

Abstract: Antarctica is the coldest, driest, and most windy continent on earth. The major terrestrial vegetation consists of cryptogams (mosses and lichens) and two vascular plant species. However, the molecular mechanism of cold tolerance and relevant regulatory networks were largely unknown in these Antarctic plants. Here, we investigated the global alterations in metabolites and regulatory pathways of an Antarctic moss (Pohlia nutans) under cold stress using an integrated multi-omics approach. We found that proline c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Nevertheless, how plants perceive cold signals remains an important question to be addressed. Plants may sense and transmit cold signals to cells through a variety of mechanisms, including reactive oxygen species (ROS), calcium (Ca 2+ ), and plant hormone signals (Liu et al, 2022). Melatonin is a pleiotropic molecule widely existing in animals and plants, which has a positive regulatory role in drought, low temperature, salinity, and other abiotic stresses (Zhan et al, 2019;Arnao and Hernańdez-Ruiz, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, how plants perceive cold signals remains an important question to be addressed. Plants may sense and transmit cold signals to cells through a variety of mechanisms, including reactive oxygen species (ROS), calcium (Ca 2+ ), and plant hormone signals (Liu et al, 2022). Melatonin is a pleiotropic molecule widely existing in animals and plants, which has a positive regulatory role in drought, low temperature, salinity, and other abiotic stresses (Zhan et al, 2019;Arnao and Hernańdez-Ruiz, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted from gill tissues of Cd-treated filefish (0 h, 12 h, 48 h, and 7 d) using TRIzol reagent (Invitrogen, Carlsbad, CA, USA). The transcriptome sequencing process was performed according to the steps we described previously [17]. Libraries were sequenced on Illumina novaseq 6000 Platform for 6G raw data and generated 150nt pair-end reads.…”
Section: Rna Extraction and Transcriptome Analysismentioning
confidence: 99%
“…The wheat OPR gene ( TaOPR1 ) can enhance the tolerance of plants to salt stress through upregulation of MYC2 transcripts, and then activate the ABA signaling pathway [ 40 ]. We also found that the OPR gene family is largely expended in the Antarctic moss Pohlia nutans [ 41 ]. In the present study, three OPR genes were upregulated by the treatment of exogenous OPDA.…”
Section: Discussionmentioning
confidence: 99%